Determinant of the Study Period for Mathematics Education Students at IAIN Bukittinggi Based on CHAID Method - Aniswita; Haida Fitri; Riswan Efendi; Lena Sastri; Pipi Rahmadani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The study period of study program graduates is one of the accreditation assessments carried out by The Independent Accreditation Agencies for Education or LAMDIK. The graduates have a study period is less than five years getting the highest point in the assessment matrix for criterion 9, namely tri-dharma outputs and achievements. However, most study program graduates from various universities in Indonesia completed their studies more than 4 years. This case also happened to graduates of Mathematics Education at IAIN Bukittinggi. There were 70% of graduates who completed their studies more than 4 years. The aim of this research was to determine factors that influence the graduates’ study period and their characteristics who were able to complete their studies for 4 years. This research was descriptive quantitative with a correlation study of 10 independent variable factors that affect the study period. By using total sampling, there were 340 graduates of Mathematics Education as a sample of this research. Documentation and questionnaires were used to collect the data. Then, the CHAID method was used to analyze the data. The result showed that, first, there were 5 independent variables that affect the graduates’ study period, namely the period of thesis completion, the gender, the major of high school, the mother’s occupation, and the track of university entrance. Second, there were 2 characteristics in which students can complete their studies for 4 years with a confidence level of 74,3%. Keywords: Study Period, Mathematics Education Students, CHAID Method